The Influence of Scientific-Based Numeracy Literacy Teaching Materials on Students’ Motivation and Higher Order Thinking Abilities - Ahmad Nizar Rangkuti; Sitompul, Lisnawati; Amran, Ali; Mara Samin Lubis; Diyah Hoiriyah; Lili Nur Indah Sari; Mariam Nasution; Sojuangon Rambe (Jurnal Pendidikan IPA Indonesia, 2024)
This research aims to analyze the influence of scientific-based numeracy literacy teaching materials on students' motivation and higher order thinking abilities. This research is a quantitative research using a quasi-experiment method with a nonequivalent control group design. Sampling used purposive sampling technique. The instruments used were motivational questionnaire sheets and higher order thinking ability tests. The paired sample t-test was used to analyze the data. The findings indicate a significant difference in the average posttest scores between the experimental group and the control group, with a significance value of 0.000<0.005 and a mean difference of 18.06 (66.00 - 47.94) between the two groups. Additionally, the confidence interval for the difference ranged from -36.959 to -30.354. That there is a significant (real) difference between the average motivation score and higher order thinking abilities of students in the experimental class and the control class using of scientific-based numeracy literacy teaching materials. So with these results it can be concluded that the scientific-based numeracy literacy teaching materials has an effect on students' motivation and higher order thinking abilities.